PEMBUKTIAN TERBALIK: SUATU KAJIAN TEORETIS TERHADAP TINDAK PIDANA KORUPSI - Agustinus Samosir (Fakultas Hukum Universitas Bangka Belitung, 2017)
The existence of reversing the burden of proof from the perspective of legislation policy is known in the criminal act of corruption as a